The fabrication of an innovative extremely sensitive nano green carbon paste electrode amended with the nanocomposite CuO/Y for electrochemical quantification of amprolium in sheep meat and liver samples. (15th August 2022) - Elgazzar, Elsayed; Said, Ragab A.M.; El-Zomrawy, Adham A.; Ashmawy, Ashraf M.; Abdel-Raoof, Ahmed M.; Mostafa, Wageha A.; Ibrahim, Hany; El-Attar, Abdul-Aziz M.M.
Highlights: Optimization of a voltammetric sensor for amprolium HCl assay. Determination of amprolium HCl preserves a healthy organization of veterinary medicine. Fast direct determination of amprolium HCl without sample preparation or derivatization. The analytical method was validated according to ICH. Abstract: In this work, carbon paste electrode (CPE) and modified CPE with copper oxide or copper yttrium oxide were prepared for determining amprolium hydrochloride (AMP) by differential pulse voltammetry. AMP has an antiprotozoal activity for treating coccidiosis in poultry; their retaining- in sheep meat and livers- induces adversative effects for the customer. XRD pattern was employed to define the fabricated nanostructured materials; the elemental composition of the nanocomposite was examined using EDX spectra. Over a pH ranging from 2 to 8, the oxidation process of AMP was studied using phosphate buffer. The scan rates were studied over a wide range (20 to 140 mV s −1 ) using cyclic voltammetry. The developed sensor shows a wide linear range (1.0 × 10 −8 –1.0 × 10 −3 M) with a detection limit of 2.32 × 10 −9 M. This method can quantify AMP in pharmaceutical form, sheep meat, and liver samples.